Maximum Ride #6 6 - Lee, NaRae; Patterson, James 1947-; Lee, JuYoun (New York : Yen Press/Hachette Book Group, 2012)
The time has come for Max and her winged "Flock" to face their ultimate enemy and discover their original purpose: to defeat the takeover of "Re-evolution," a sinister experiment to re-engineer a select population into a scientifically superior master race...and to terminate the rest.
Keywords: Patterson, James, -- 1947- -- Adaptations; Genetic engineering -- Comic books, strips, etc; Kidnapping -- Comic books, strips, etc; Teenagers -- Comic books, strips, etc; Comic books, strips, etc -- United States; Graphic novels -- United States; Genetic engineering -- Fiction; Kidnapping -- Fiction; Teenagers -- Fiction; Adventure and adventurers -- Fiction; Cartoons and comics; Science fiction comic books, strips, etc; Comic books, strips, etc; Graphic novels